Numeracy Literacy Question Board as an Innovative Media for Interest in Learning Indonesian at Madrasah Ibtidaiyah - Amreta , Midya Yuli; Lestari, Nanik Indah; Mukholifah , Siti; Putri, Erly Sintia; Lutfiyah , Halimatu; Rahmatika , Chafidatur (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This research is based on the need for innovation in learning media to increase interest in learning Indonesian that is integrated with literacy and numeracy skills in Madrasah Ibtidaiyah. Some challenges in literacy and numeracy faced by 4th-grade students include: 1) low student enthusiasm in literacy and numeracy learning; 2) lack of students' ability to connect number values with everyday situations; 3) lack of learning media that can integrate literacy and numeracy activities in a fun way. The purpose of this study is to explain the various functions of the innovative media, the Numeracy Literacy Question Board, as a tool for learning Indonesian. The research was conducted in the even semester of the 2024/2025 academic year at MIS Ummi Kamilah Sunan Drajat, located in Bubulan District, Bojonegoro Regency, East Java Province. This study employs a qualitative approach using non-test instruments, including interview guidelines, observation guidelines, and documentation. All research instruments were compiled using objective and systematic procedures. Participants in the study included the madrasah principal, class teachers, and students. The research data was analyzed using a thematic approach. The research findings indicate that the implementation of the numerical literacy problem board media functions to: 1) ensure orderly learning; 2) increase student participation and enthusiasm; 3) improve student reading comprehension; and 4) develop integrated learning